2003
DOI: 10.1021/np0204489
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial Activity of Phorbol Esters from the Fruits of Sapium indicum

Abstract: Three new phorbol esters, 12-(2-N-methylaminobenzoyl)-4beta,5,20-trideoxyphorbol-13-acetate (1), 12-(2-N-methylaminobenzoyl)-4alpha,5,20-trideoxyphorbol-13-acetate (2), and 12-(2-N-methylaminobenzoyl)-4alpha, 20-dideoxy-5-hydroxyphorbol-13-acetate (6), together with six known compounds (3-5 and 7-9), were isolated from the fruits of Sapium indicum. The chemical structures of 1, 2, and 6 were elucidated by analysis of their spectroscopic data. Compounds 1-3, 5, and 7-9 exhibited antimycobacterial activity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 11 publications
3
49
0
1
Order By: Relevance
“…2). The coupling constant between H-11 and H-12 was 9.7 Hz, confirming the a configuration of H-12 (Chumkaew et al, 2003). Other characteristic resonances included signals for a tiglyl group and an acetyl moiety.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…2). The coupling constant between H-11 and H-12 was 9.7 Hz, confirming the a configuration of H-12 (Chumkaew et al, 2003). Other characteristic resonances included signals for a tiglyl group and an acetyl moiety.…”
Section: Introductionmentioning
confidence: 59%
“…In addition, NMR signals for a hexadecanoyl group in 2 were observed to replace those for an acetyl moiety in 1. Other characteristic resonances included signals for a tiglyl group (Zhang et al, 2013;Chumkaew et al, 2003). In the HMBC spectrum, H-12 proton showed a 3 J correlation with the carbonyl carbon of the tiglyl group, confirming the location of the tiglyl group at C-12.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Therefore, J. curcas seeds are unsuitable for being used in animal feeding [11]. Despite their toxicity, phorbol esters also offer many interesting activities including insecticidal, molluscicidal and anti-mycobacterial [12][13][14]. A recent study has demonstrated that Casbene Synthase plays a significant role in the synthesis of phorbol esters [15].…”
Section: Introductionmentioning
confidence: 99%